2013
DOI: 10.1002/ijc.28026
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of proliferative and migratory genes in regulatory T cells from patients with metastatic castration‐resistant prostate cancer

Abstract: A higher frequency of regulatory T cells (Tregs) has been observed in peripheral blood mononuclear cells (PBMC) of patients with different types of solid tumors and hematological malignancies as compared to healthy donors. In prostate cancer patients, Tregs in PBMC have been shown to have increased suppressive function. Tumor-induced biological changes in Tregs may enable tumor cells to escape immunosurveillance. We performed genome-wide expression analyses comparing the expression levels of more than 38,500 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…In prostate cancer patients, increased CD4 + CD25 + regulatory T cells (Treg cells) are found in tumour tissue as well as in serum at the time of radical prostatectomy or in the castration-resistant stage with metastases. These Treg cells hinder the body's own immune activity of T cells against the tumour [18,[33][34][35]. In prostate cancer, the growth, migration and adhesion of prostate cancer cells are reinforced by the effect of IL-6 on androgen receptors [19].…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer patients, increased CD4 + CD25 + regulatory T cells (Treg cells) are found in tumour tissue as well as in serum at the time of radical prostatectomy or in the castration-resistant stage with metastases. These Treg cells hinder the body's own immune activity of T cells against the tumour [18,[33][34][35]. In prostate cancer, the growth, migration and adhesion of prostate cancer cells are reinforced by the effect of IL-6 on androgen receptors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have investigated intragraft macrophages, though many investigations have focused on murine models of cardiac transplantation (34)(35)(36). Wu et al interrogated macrophage polarization in transplant rejection (35) and found that graft-infiltrating macrophages in a murine model of chronic cardiac transplant rejection demonstrated an M2 (IL-4) phenotype; they reported that blocking the recep- tor P2X7, which may be upregulated in M2 macrophages, improved long-term cardiac allograft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Among the RGS proteins that modulate the function of heterotrimeric G proteins by stimulating the GTPase activity of G-protein a subunits, RGS10, a 20-kDa protein identified in 1996 by Hunt and coworkers, enhances the GTP hydrolytic activity of several members of the Ga i family, including Ga i3 , Ga q , and Ga z , but fails to associate with the structurally and functionally different Ga s subunit (Hunt et al, 1996;Popov et al, 1997). RGS10 belongs to the R12 subfamily of RGSs and shares with other RGS proteins the conserved 120 amino acid sequence termed the RGS domain, which, in the case of RGS10, has been reported to be fully active per se, showing a similar GAP activity than the full-length RGS10 (Ali et al, 2013;Cacan et al, 2014;Intini et al, 2014;Lee et al, 2012a;Mao et al, 2014;Popov et al, 1997;Rivero et al, 2013).…”
Section: Rgs10mentioning
confidence: 98%
“…T-cell-dependent antigens produced a delayed antibody response in RGS1 knockout mice . RGS1 has been shown to be involved in chemokine-mediated homing of lymphocytes to secondary lymphoid organs, such as the intestinal mucosa, as well as their localization and movement within lymphoid organ during the immune response (Gibbons et al, 2011;Huen et al, 2013;Wierenga et al, 2014).…”
Section: Rgs1mentioning
confidence: 99%